ORIGINAL PAPER Patient with acute myocardial infarction with ST-segment elevation hospitalized more than 12 hours from the onset of symptoms: should we consider invasive treatment? Analysis of PL-ACS Registry - Gierlotka, Marek; Gąsior, Mariusz; Wilczek, Krzysztof; Kalarus, Zbigniew; Poloński, Lech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2005)
The data on efficacy of coronary angioplasty (PCI) in patients with ST-segment elevation myocardial infarction (STEMI) with symptom-onset-to-presentation time of more than 12 hours are limited and recommendations are imprecise in this group of patients. The aim of this analysis was to present treatment options in STEMI patients hospitalized more than 12 hours after symptom onset, with particular focus on PCI procedures and their results. Methods: All patients with STEMI registered in the Polish Registry of Acute Coronary Syndromes (PL-ACS) during 12 months period (from October 2003 to September 2004) were included in the analysis. Results: ST-segment elevation myocardial infarction was present in 5 066 patients (34.7%) included in the Registry and about one quarter of these patients were admitted to hospital more than 12 hours after the onset of symptoms. Among patients with symptom-onset-to-admission time exceeding 12 hours 308 patients (24.6%) were treated invasively (early coronary angiography). They were about 7 years younger and there were fewer females as compared to patients treated non-invasively. Cardiogenic shock was noted in 10.3% and 11.0%, respectively, in invasive and non-invasive groups. In-hospital (6.8% vs. 16.8%; p<0.0001) as well as 30-day mortality (8.0% vs. 19.7%; p<0.0001) was lower in patients treated invasively. The rates of recurrent myocardial infarction, stroke and major bleeding were similar in both groups. In patients with symptom-onset-to-admission time exceeding 12 hours invasive strategy was an independent predictor of lower 30-day mortality (relative risk = 0.57; 95% confidence interval = 0.37-0.88; p=0.011). Conclusions: In selected patients with ST-segment elevation myocardial infarction and symptom-onset-to- -admission time exceeding 12 hours invasive strategy may lead to lower short-term mortality. At present, patients treated invasively are pre-selected and their initial risk is lower as compared to those treated non-invasively.